THE RELATIONSHIP OF LIQUIDITY, DEBT AND SHARIA STOCK INVESTMENT’S RISK MODERATED BY FINANCIAL PERFORMANCE - Riskin Hidayat (istinbath, 2021)
This study aims to test the effect of liquidity and debt on Sharia stock investment’s risk moderated by the financial performance of the Jakarta Islamic Index firm. The population in this study are all Jakarta Islamic Index firms listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique uses purposive sampling and obtained a sample of 110. Data are obtained from Indonesia Stock Exchange. Data analysis uses moderating regression analysis. The results show that liquidity has a significant negative influence on sharia stock investment risk, meanwhile debt has a significant positive effect on sharia stock investment risk. Liquidity is more sensitive to investment risk in high-performing firms than low-performing firms, while debt is more sensitive to the risk of investing in stocks in low-performing firms than high-performing firms.